Building a University Brand Community: The Long-Term Impact of Shared Experiences - McAlexander,Jim; Koenig,Hal; Schouten ,John W. (Journal of Marketing for Higher Education, 2004)
Relationship marketing has made its way into the practices of university administrations. With it have also arrived many problems associated with the aggressive use of CRM technologies. One particularly effective and healthy approach to relationship marketing in higher education is to treat the university, with all of its stakeholders, as a brand community, and to pursue policies and programs to strengthen the relationships that define the community. With this paper, we examine an important class of relationship often neglected in the CRM literature, i.e., the relationships among the customers who support the brand and who ultimately give it its meaning and vitality. Specifically, we explore how the nature of relationships among students affects their long-term loyalty to a university. The results of a telephone survey of university alumni demonstrate the importance of certain types of university experiences on student relationships and, thereafter, on loyalty to their alma mater and their intentions to support the university in the future.
Keywords: Marketing